METHODICAL SYSTEM OF STUDENTS TRAINING OF ECONOMIC DISCOURSE TRANSLATION FROM THE CHINESE LANGUAGE TO RUSSIAN ON THE BASIS OF MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES - Malankhanova, A.E. (Tambov University Review. Series: Humanities, 2016)
For effective training of future translators from Chinese into Russian, in particular in the economic sphere it is necessary to develop methodological training system based on the analysis of existing methods of teaching of foreign languages and translation. The definitions of the main components of methodical system of training for this kind of translation: preconditions; approaches (system, competence-based, student-activity and communicative and cognitive); principles (of visibility, accessibility, innovation, information, problem, profile orientation, functionality, taking into account the native language); and teaching methods (communicative, problem, interactive), organizational forms of teaching, quality criteria and evaluation, learning content, psychological and pedagogical conditions are provided. According to them, a structure of the methodical system is suggested: preconditions, the target unit, the theoretical unit, technological and assessment and productive units. Due to the lack of development and researches in the field of education in the sphere of economic discourse translation from Chinese into Russian taking into account its features (lexical, syntactic and stylistic) our methodical system helps to improve teaching of students to prepare them for work in the market of professional translation services.